Method for laser shock peening regulation of low-density steel taking into account hot rolling pre-deformation history

CN122941874APending Publication Date: 2026-10-20NANCHANG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611228788.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]针对上述现有技术存在的问题,本发明提供了考虑热轧预变形历史的低密度钢激光冲击强化调控方法,实现了材料初始组织状态的精准界定,解决了现有技术忽略热轧预变形组织差异、工艺匹配盲目性的问题

Benefits of technology

本发明基于热轧总压下量的Fe-Mn-Al-C低密度钢预变形分级标准,量化区分低、中、高预变形基材的位错密度区间、变形带分布形貌、纳米κ碳化物尺寸与梯度分布特征,实现了材料初始组织状态的精准界定,解决了现有技术忽略热轧预变形组织差异、工艺匹配盲目性的问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

This invention discloses a laser shock peening control method for low-density steel that considers the pre-deformation history of hot rolling, relating to the field of laser shock peening control. The method includes: S1, preparing Fe-Mn-Al-C low-density steel hot-rolled substrates; S2, determining the microstructure and plastic energy storage characteristics of substrates with different pre-deformation grades; S3, implementing laser shock peening with corresponding parameters on substrates of different pre-deformation grades under unified laser shock peening conditions; and S4, performing post-processing on the samples after shock peening. Based on the pre-deformation grading standard for Fe-Mn-Al-C low-density steel with total hot rolling reduction, this invention quantitatively distinguishes the dislocation density range, deformation zone distribution morphology, and nano-κ carbide size and gradient distribution characteristics of low, medium, and high pre-deformation substrates, achieving precise definition of the initial microstructure of the material and solving the problems of neglecting the differences in hot-rolled pre-deformation microstructure and the blind matching of processes in existing technologies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of laser shock strengthening and control technology, and specifically to a method for controlling laser shock strengthening of low-density steel that takes into account the pre-deformation history of hot rolling. Background Technology

[0002] Fe-Mn-Al-C series low-density high-strength steels, with their advantages of low density, high specific strength, and excellent strength-ductility balance, have broad application prospects in aerospace, rail transportation, and lightweight structures for high-end equipment. These steels achieve excellent mechanical properties through a high-manganese austenitic matrix, aluminum solid solution strengthening, and nano-κ carbide precipitation strengthening. However, different reduction rates during hot rolling processes can lead to significant differences in microstructure gradients and plastic energy storage, directly affecting subsequent surface strengthening effects and high-cycle fatigue performance.

[0003] Laser shock peening is a highly efficient metal surface modification technology that can significantly improve the fatigue life of metal components by inducing surface dislocation multiplication and introducing deep residual compressive stress through high-pressure shock waves. Currently, laser shock peening processes for Fe-Mn-Al-C low-density steel all use uniform and fixed laser energy and fixed number of impact passes for full-domain strengthening, completely ignoring the intrinsic material differences caused by the hot rolling pre-deformation history.

[0004] In actual hot rolling, different total reduction amounts will cause three major microstructure differences in the substrate: First, the range of hot rolling reduction amounts will lead to a difference of nearly one order of magnitude in the initial dislocation density of the matrix; second, the deformation bands will exhibit completely different distribution patterns, such as discontinuous sparseness or continuous penetration and high-density interweaving; and third, the size, surface enrichment degree, and thickness gradient distribution of nano-κ carbides will vary significantly, ultimately causing the plastic energy storage of different hot-rolled substrates to exhibit obvious low, medium, and high stratification.

[0005] Existing fixed-parameter laser shock blasting processes have unresolved issues: for substrates with low pre-deformation and low energy storage, the fixed-parameter shock wave pressure is insufficient, resulting in inadequate plastic deformation, shallow residual compressive stress layer, and sparse dislocation strengthening network, leading to insufficient strengthening and low fatigue gain; for substrates with high pre-deformation and high energy storage, the matrix itself has dense dislocations and extremely high plastic energy storage, and the same laser shock load will cause dislocation over-multiplication, nano-carbide fragmentation, matrix interface cracking, and surface microcrack initiation, leading to over-impact damage, stress relaxation, and fatigue performance degradation; medium-pre-deformation substrates are prone to problems such as poor strengthening stability and large batch performance fluctuations.

[0006] To address these issues, we offer a laser shock strengthening control method for low-density steel that considers the pre-deformation history of hot rolling. Summary of the Invention

[0007] To address the problems of the existing technologies, this invention provides a laser shock strengthening control method for low-density steel that takes into account the hot-rolled pre-deformation history. This method achieves precise definition of the initial microstructure of the material and solves the problems of neglecting the differences in the microstructure of hot-rolled pre-deformation and the blind matching of processes in the existing technologies.

[0008] To achieve the above objectives, the present invention employs a laser shock strengthening control method for low-density steel that considers the hot-rolled pre-deformation history, comprising: S1. Preparation of Fe-Mn-Al-C low-density steel hot-rolled base material, wherein the chemical composition of the low-density steel by mass fraction is: C 0.5%~1.0%, Mn 15%~22%, Al 7.5%~10%, with the balance being Fe and trace impurities, and the total mass fraction of trace impurities S and P ≤0.03%; the Fe-Mn-Al-C low-density steel of the present invention, within the range of C, Mn, and Al composition, according to thermodynamic equilibrium phase diagram calculation and experimental verification, has the following high-temperature microstructure characteristics: no single austenite phase region in the temperature range of 600-1600℃, and the hot working window is in the austenite + ferrite dual-phase region, belonging to austenite-based dual-phase steel; Based on the total hot-rolled reduction, the hot-rolled substrate is pre-deformed and classified into low-pre-deformed substrate, medium-pre-deformed substrate, and high-pre-deformed substrate. S2. Based on the microstructure and plastic energy storage characteristics of substrates with different pre-deformation grades, differentially couple and match the dual process parameters of laser single pulse energy and laser shock pass. S3. Under the same laser shock conditions, laser shock strengthening with corresponding parameters is carried out on pre-deformed substrates of different grades. S4. After the impact, the sample is post-treated to obtain Fe-Mn-Al-C low-density steel components with no surface micro-damage, stable deep residual compressive stress, and high fatigue life.

[0009] As a further optimization of the above scheme, the pre-deformation grading standard in step S1 is as follows: Low pre-deformation substrate: total hot rolling reduction ≤30%, matrix dislocation density <5×10 9 cm -2 The deformation bands are discontinuously and sparsely distributed, the size of the nano-κ carbides is 50-120 nm, the thickness gradient is weak, and the matrix has low plastic energy storage. Pre-deformed substrate: hot-rolled total reduction of 30%–60%, matrix dislocation density of 5×10⁻⁶ 9 ~2×10 10 cm -2 The continuous and uniform deformation bands penetrate the grains, the size of the nano-κ carbides is 30-80 nm, the thickness gradient is significant, and the matrix has moderate plastic energy storage. High pre-deformation substrate: total hot rolling reduction > 60%, matrix dislocation density > 2 × 10⁻⁶10 cm -2 The high-density interwoven deformation bands are distributed throughout the grains, the nano-κ carbides are 20-50nm in size and highly enriched on the surface, and the matrix has high plasticity and energy storage.

[0010] As a further optimization of the above scheme, the differentiated process matching criterion in step S2 is as follows: Low pre-deformation substrate: matched with high single-pulse energy, 3-pass repetitive laser shock; Medium-deformation substrate: matched with medium single-pulse energy, 2-pass repetitive laser shock; High pre-deformation substrate: matched with low single-pulse energy, 1-pass single-shot laser shock.

[0011] As a further optimization of the above scheme, the single-pulse laser energy of the low pre-deformation substrate is 9J, and the peak pressure of the shock wave is 2.6GPa; The single-pulse laser energy of the pre-deformed substrate is 7J, and the peak pressure of the shock wave is 2.1GPa. The single-pulse laser energy of the high pre-deformation substrate is 5J, and the peak pressure of the shock wave is 1.5GPa.

[0012] As a further optimization of the above scheme, the unified laser shock conditions in step S3 include: An Nd:YAG pulsed laser with a wavelength of 1064 nm and a pulse width of 15 ns was used. A 150 μm high-purity aluminum foil was pasted on the sample surface as an absorption layer. A 1 mm thick continuously flowing deionized water layer was placed above the sample as a transparent constraint layer with a flow rate of 0.8 L / min. The laser spot diameter was 3 mm, and a square scanning path was used with an overlap rate of 50% between adjacent spots.

[0013] As a further optimization of the above scheme, the post-processing method in step S4 is as follows: After laser shock, the aluminum foil was peeled off, and the sample was ultrasonically cleaned with anhydrous ethanol for 5 minutes, then water-cooled and dried for later use.

[0014] As a further optimization of the above scheme, the low-density steel hot rolling preparation process includes: the first step, alloy melting and ingot casting; the raw materials are distributed according to the target composition, melted in a vacuum induction melting furnace, and cast into cylindrical ingots; The second step is homogenization annealing and hot forging; the round ingot is homogenized at 1200℃ to eliminate casting segregation, and then multi-directional hot forging is performed to forge it into a shape with a uniform initial thickness H. 00 Square or rectangular billets are forged and then air-cooled to room temperature; The third step is to prepare slabs with different initial thicknesses by wire cutting. From the billet forged in the second step, several slabs with different initial thicknesses H0 are processed by wire cutting. This cutting method does not introduce any macroscopic plastic deformation, ensuring that all slabs perfectly inherit the consistent initial structure of the parent material. The fourth step is uniform firing and differentiated hot rolling; after all slabs are uniformly fired at 1200℃, different initial slab thicknesses are matched with different total hot rolling reduction rates, and all slabs are uniformly rolled to the same target plate thickness H. t Final rolling temperature ≥900℃; Method for determining the uniform temperature through-firing process: Place all slabs with different initial thicknesses H0 in the same heating furnace and heat them at the same target temperature of 1200℃. The holding time t of each slab is set according to the empirical formula t=k×H0, where k is the heating coefficient, with a value range of 1.0-2.0min / mm, and H0 is the initial thickness of the slab, in mm. When the target temperature T = 1150℃, and k = 1.5 min / mm is selected: For a slab with H0=12mm, the holding time is t=18min; For a slab with H0=20mm, the heat preservation time is t=30min; This formula ensures that the core of all slabs reaches the target temperature, so that all slabs obtain an initial microstructure with consistent proportions, uniform grain size, and uniform composition distribution, and completes austenite homogenization to obtain an initial microstructure with consistent grain size, while avoiding overheating of thin slabs or insufficient homogenization of thick slabs. The fifth step is to force rapid cooling to lock in the microstructure; after hot rolling, rapid water cooling to room temperature can suppress dislocation recovery, static recrystallization and large-scale precipitation of the second phase at high temperature, and stabilize the dislocation substructure and deformation energy storage generated by hot rolling plastic deformation. Step 6: Low-temperature stress relief; The cooled hot-rolled sheet is subjected to low-temperature recovery stress relief annealing to release only the macroscopic residual stress caused by hot rolling, while retaining the dislocation substructure, deformation energy storage and original phase distribution introduced by different hot rolling reduction amounts. The holding temperature for low-temperature stress-relief annealing is 200~300℃, the holding time is 0.5~1.5h, and the cooling method is water cooling. Within this temperature range, the main purpose is to eliminate macroscopic internal stress and improve the plate shape, without causing significant dislocation annihilation or κ carbide coarsening.

[0015] Step 7, surface treatment; double-sided fine grinding, controlling the roughness Ra≤1.6μm, the surface presents a uniform and delicate matte surface, ultrasonic cleaning with anhydrous ethanol for 15min to remove oil and grinding debris, and drying; Step 8: Differentiated laser shock.

[0016] The laser shock strengthening control method for low-density steel that takes into account the hot-rolled pre-deformation history of the present invention has the following beneficial effects: This invention is based on the pre-deformation grading standard of Fe-Mn-Al-C low-density steel with total hot rolling reduction. It quantitatively distinguishes the dislocation density range, deformation zone distribution morphology, and nano-κ carbide size and gradient distribution characteristics of low, medium and high pre-deformation substrates, and achieves accurate definition of the initial microstructure of the material. It solves the problems of neglecting the differences in microstructure of hot-rolled pre-deformation and the blind matching of processes in the prior art. This invention employs a dual-variable coupling and differentiated control strategy of laser energy and impact pass frequency to replace the traditional single fixed parameter process: low pre-deformation substrates use high-energy multi-passes to supplement plastic deformation and construct a deep stable residual compressive stress field; medium pre-deformation substrates use medium-energy two-passes to achieve a balance between strengthening effect and microstructure integrity; high pre-deformation substrates use low-energy single-passes for mild modification, completely avoiding the risk of over-impact cracking in high-energy-storage substrates, and overcoming the long-standing contradiction between "insufficient strengthening" and "over-impact failure" in traditional processes.

[0017] This invention achieves a composite dense strengthening structure of hot-rolled original deformation zone and laser-induced dislocation network through a graded matching process. It fully preserves the nano-κ carbide precipitation strengthening phase, avoids carbide breakage, interface debonding and surface microcrack defects, and significantly improves the dislocation strengthening effect and the effective depth of residual compressive stress while ensuring no damage to the material surface. The stability of the strengthened structure is also improved.

[0018] By standardizing the finished substrate thickness, controlling the reduction rate with differentiated billet thickness, using rapid water cooling and low-temperature stress relief, interference from non-pre-deformation variables is eliminated, thereby improving the stability and repeatability of the laser shock strengthening process.

[0019] Specific embodiments of the present invention are disclosed in detail with reference to the following description and accompanying drawings, indicating how the principles of the present invention can be adopted. It should be understood that the embodiments of the present invention are not limited in scope as a result, and that the embodiments of the present invention include many changes, modifications and equivalents within the spirit and scope of the appended claims. Attached Figure Description

[0020] Figure 1 This is a flowchart illustrating the steps of the laser shock strengthening control method for low-density steel that takes into account the hot-rolled pre-deformation history, as described in this invention. Detailed Implementation

[0021] The chemical composition of the Fe-Mn-Al-C low-density steel used in this invention, by mass fraction, is: C 0.5%~1.0%, Mn 15%~22%, Al 7.5%~10%, with the balance being Fe and trace impurities S and P, and the total mass fraction of trace impurities ≤0.03%.

[0022] Please refer to the instruction manual appendix. Figure 1 This invention provides a technical solution: a method for controlling laser shock strengthening of low-density steel considering hot-rolled pre-deformation history, comprising: Existing laser shock annealing only fixes the laser energy and shock pass to a uniform degree, ignoring the differences in microstructure caused by the three major gradients of hot rolling pre-deformation: 1. Different total hot rolling reductions result in an order-of-magnitude difference in the initial dislocation density of the matrix; 2. The continuous or discontinuous distribution of deformation zones has completely different patterns; 3. The size, surface enrichment, and thickness gradient distribution of nano-κ carbides vary greatly.

[0023] Traditional fixed-parameter impact has an irreconcilable contradiction: high pre-deformation substrates have extremely high plastic energy storage and dense dislocation networks. Under the same laser shock wave pressure, they will cause dislocations to multiply violently, carbides to break up, and microcracks to emerge on the surface, resulting in impact fatigue failure; low pre-deformation substrates have fewer initial dislocations and larger carbides. Under the same parameters, the amount of plastic deformation is insufficient, the residual compressive stress layer is shallow, and the fatigue gain is low.

[0024] This invention uses the total hot rolling reduction as the grading criterion to accurately classify pre-deformed matrices into three categories: low, medium, and high. It quantifies the corresponding initial dislocation density, deformation zone morphology, and κ carbide gradient characteristics to establish a quantitative grading standard for microstructure. Differential coupling is used to match the dual variables of single-pulse laser energy and impact repetition frequency, rather than adjusting only the energy or frequency; low pre-deformation uses high-energy multi-pass to supplement plastic deformation and build deep residual compressive stress; medium pre-deformation uses medium-energy two-pass to balance strengthening and tissue damage; high pre-deformation uses low-energy single-pass to achieve mild surface modification and avoid energy storage overload cracking. By synergistically regulating the absorption layer and the constraint layer to match the shock wave attenuation rate, and combining it with a graded process, a composite dense strengthening structure of the original hot-rolled deformation zone and the laser-induced dislocation network is achieved. The complete strengthening phase of nano-κ carbide is preserved, and deep stable residual compressive stress, no surface micro-damage, and a significant improvement in fatigue life are achieved simultaneously, solving the dual problem of "insufficient strengthening" and "over-impact failure" in traditional processes.

[0025] The laser shock testing conditions for this invention are as follows: An Nd:YAG pulsed laser with a wavelength of 1064 nm and a pulse width of 15 ns is used; a 150 μm high-purity aluminum foil is adhered to the surface of the sample to be strengthened as an absorption layer; a 1 mm thick layer of deionized water continuously flows above the sample as a transparent constraint layer with a flow rate of 0.8 L / min; the laser spot diameter is 3 mm, the spot has a square scanning path, and the overlap rate between adjacent spots is fixed at 50%; after laser shock testing, the aluminum foil is removed, the sample is ultrasonically cleaned with anhydrous ethanol for 5 min, and then water-cooled and dried for later use; TEM is used to observe the surface dislocation density, κ carbide morphology, and size distribution; X-ray stress meter is used to detect residual compressive stress along the thickness gradient; and a rotary bending fatigue testing machine is used for 10... 7 Cycle fatigue life; laser shock wave pressure is calibrated using a piezoelectric sensor.

[0026] Three pre-deformation grading standards are used for three types of deformed hot-rolled substrates: The first type is a low-pre-deformation hot-rolled substrate: total hot-rolling reduction ≤30%, matrix dislocation density <5×10⁻⁶. 9 cm -2 The deformation bands are discontinuously and sparsely distributed, the κ carbide size is 50-120 nm and weak along the thickness gradient, and the matrix has low plastic energy storage; matching criteria: high single pulse energy and 3 repeated impacts. The second type is a pre-deformed hot-rolled substrate: the total hot-rolling reduction is 30%–60%, and the matrix dislocation density is 5×10⁻⁶. 9 ~2×10 10 cm -2 Continuous and uniform deformation bands penetrate the grains; κ carbide size is 30–80 nm with a significant thickness gradient; moderate plastic energy storage; matching criteria: medium single-pulse energy, 2 repeated impacts. The third type is high-pre-deformation hot-rolled substrate: total hot-rolling reduction > 60%, matrix dislocation density > 2 × 10⁻⁶. 10 cm -2 High-density interwoven deformation bands are distributed throughout the grains, with ultrafine κ carbides of 20-50 nm and highly enriched on the surface, resulting in extremely high plastic energy storage; matching criteria: low single-pulse energy, 1 single-impact.

[0027] The first step is alloy melting and casting; the alloy is prepared according to the target composition, melted in a vacuum induction melting furnace, and cast into cylindrical ingots. The second step is homogenization annealing and hot forging; the round ingot is homogenized at 1200℃ to eliminate casting segregation, and then multi-directional hot forging is performed to forge it into a shape with a uniform initial thickness H. 00 Square or rectangular billets are forged and then air-cooled to room temperature; The third step is to prepare slabs with different initial thicknesses by wire cutting. From the billet forged in the second step, several slabs with different initial thicknesses H0 are processed by wire cutting. This cutting method does not introduce any macroscopic plastic deformation, ensuring that all slabs perfectly inherit the consistent initial structure of the parent material. The fourth step is uniform firing and differentiated hot rolling; after all slabs are uniformly fired at 1200℃, different initial slab thicknesses are matched with different total hot rolling reduction rates, and all slabs are uniformly rolled to the same target plate thickness H. t Final rolling temperature ≥900℃; Method for determining the uniform temperature through-firing process: Place all slabs with different initial thicknesses H0 in the same heating furnace and heat them at the same target temperature of 1200℃. The holding time t of each slab is set according to the empirical formula t=k×H0, where k is the heating coefficient, with a value range of 1.0-2.0min / mm, and H0 is the initial thickness of the slab, in mm. When the target temperature T = 1150℃, and k = 1.5 min / mm is selected: For a slab with H0=12mm, the holding time is t=18min; For a slab with H0=20mm, the heat preservation time is t=30min; This formula ensures that the core of all slabs reaches the target temperature, so that all slabs obtain an initial microstructure with consistent proportions, uniform grain size, and uniform composition distribution, and completes austenite homogenization to obtain an initial microstructure with consistent grain size, while avoiding overheating of thin slabs or insufficient homogenization of thick slabs. The fifth step is to force rapid cooling to lock in the microstructure; after hot rolling, rapid water cooling to room temperature can suppress dislocation recovery, static recrystallization and large-scale precipitation of the second phase at high temperature, and stabilize the dislocation substructure and deformation energy storage generated by hot rolling plastic deformation. In Fe-Mn-Al-C steel, the precipitation of κ carbides is sensitive to temperature and cooling rate. Air cooling is slow, which can lead to dislocation recovery and increased recrystallization. It may also cause uneven growth of κ carbides or precipitation along grain boundaries, which seriously weakens the strengthening potential of subsequent laser shock. After hot rolling, rapid cooling (such as water cooling or laminar flow cooling) should be used to freeze deformed dislocations and fine κ carbides, and retain the pre-deformed structure with high-density defects. Step 6: Low-temperature stress relief; The cooled hot-rolled sheet is subjected to low-temperature recovery stress relief annealing to release only the macroscopic residual stress caused by hot rolling, while retaining the dislocation substructure, deformation energy storage and original phase distribution introduced by different hot rolling reduction amounts. Hot-rolled water-cooled sheets have huge macroscopic bending residual stress. If low-temperature stress-relieving annealing is not performed, this stress will be superimposed with LSP shock wave stress, and the residual stress test data will be completely distorted. It will be impossible to distinguish between "hot-rolled original stress" and "LSP strengthening stress", and it will be difficult to accurately quantify the regulatory effect of initial pre-deformation on gradient structure and fatigue performance. The holding temperature for low-temperature stress-relief annealing is 200~300℃, the holding time is 0.5~1.5h, and the cooling method is water cooling. Within this temperature range, the main purpose is to eliminate macroscopic internal stress and improve the plate shape, without causing significant dislocation annihilation or κ carbide coarsening.

[0028] Step 7, surface treatment; double-sided fine grinding, controlling the roughness Ra≤1.6μm, the surface presents a uniform and delicate matte surface, ultrasonic cleaning with anhydrous ethanol for 15min to remove oil and grinding debris, and drying; Step 8: Differentiated laser shock.

[0029] The Fe-Mn-Al-C low-density steel of this invention, within the range of C, Mn, and Al composition, has the following high-temperature microstructure characteristics as verified by thermodynamic equilibrium phase diagram calculation and experiments: there is no single austenite phase region in the temperature range of 600-1600℃, and the hot working window is in the austenite + ferrite dual-phase region, belonging to austenite-based dual-phase steel.

[0030] In practice: Example 1

[0031] Laser shock strengthening and control of low-density Fe-Mn-Al-C steel with low hot-rolled pre-deformation (total hot-rolled reduction of 25%, low pre-deformation substrate).

[0032] Step 1: Prepare low-pre-deformation hot-rolled low-density steel substrate; Steel composition (mass fraction): C (carbon) 0.65%, Mn (manganese) 18.2%, Al (aluminum) 8.3%, balance Fe (iron), S (sulfur) 0.012%, P (phosphorus) 0.010%; Melting and casting cylindrical ingots; homogenizing annealing of the ingots at 1200℃ to eliminate casting segregation, hot forging followed by air cooling; wire cutting to obtain slabs of initial thickness; slabs subjected to through-heating at 1200℃ with differentiated heat treatment, hot rolling with a total reduction of 25%, uniformly rolled to the target thickness, with a final rolling temperature ≥900℃; rapid water cooling after rolling; low-temperature stress-relief annealing at 200~300℃; double-sided precision grinding to Ra≤1.6μm, ultrasonic cleaning and drying; Wire EDM is used to process standard rotary bending fatigue specimens, with a gauge length of Φ8mm×20mm. TEM analysis of the microstructure in the hot-rolled state: dislocation density 3.2 × 10⁻⁶ 9 cm -2It has a small number of discontinuous deformation bands, with an average κ carbide size of 92 nm. It is only slightly enriched near the surface, and the core carbide is evenly distributed with low plastic energy storage.

[0033] Step 2: Differentiated coupling matching laser shock process; The laser single pulse energy is 9J, the laser impact is 3 passes, the single full-area scan covers the entire enhanced area and then the impact is repeated, and the three scan paths completely overlap. The peak pressure of the shock wave was calibrated to be 2.6 GPa; The remaining general supporting conditions adopt the same standard (150μm aluminum foil absorption layer, 1mm flowing water constraint layer, 3mm light spot, 50% overlap rate, 15ns pulse width, 1064nm wavelength).

[0034] Step 3: Post-processing and performance testing; After the impact is complete, peel off the aluminum foil, ultrasonically clean with anhydrous ethanol for 5 minutes, and then dry with water. Residual compressive stress was measured at 20 μm points along the sample thickness from 0 to 200 μm. TEM was used to observe the surface microstructures in the 0–80 μm and 80–150 μm ranges, respectively. Rotary bending fatigue testing machine was used to test stress amplitude of 450 MPa for 10 hours. 7 Weekly fatigue life.

[0035] Detection results of Example 1: The maximum residual compressive stress on the surface of the steel sample is 486 MPa, the depth of the residual compressive stress layer is 128 μm, and the stable compressive stress of 312 MPa is maintained at a depth of 100 μm. The dislocation density on the surface of the steel sample increased to 1.1 × 10⁻⁶. 11 cm -2 The original sparse discontinuous deformation bands and laser-induced high-density dislocations intertwine to form a continuous three-dimensional strengthening network; The κ carbide exhibits no fragmentation, no coarsening, and no interfacial microcracks, and fully retains the nano-precipitated strengthening phase. 10 7 The high-cycle fatigue life was increased by 212% compared with the unimpacted hot-rolled substrate; the surface and subsurface of the sample were free of any microcracks, interlaminar delamination, carbide cracking and other over-impact defects. Comparison of two sets of traditional unified parameters: Comparison 1 (traditional fixed 2 passes, 7J): fatigue life only increased by 105%, residual compressive stress layer was only 72μm, and the strengthening depth was insufficient; Comparison 2 (forced 3 passes at 5J low energy): Insufficient shock wave pressure, inadequate surface plastic deformation, and fatigue life increased by 93%; This invention demonstrates that by employing a high-energy and multi-pass coupling scheme for low-pre-deformation substrates, it can simultaneously realize deep residual compressive stress and dense composite dislocation networks, solving the problems of insufficient strengthening and low fatigue gain in small-pre-deformation components. Existing single-variable adjustment processes cannot achieve the same strengthening effect.

[0036] Example 2 Laser shock strengthening and control of medium hot-rolled pre-deformed Fe-Mn-Al-C low-density steel (total hot-rolling reduction 48%, medium pre-deformed substrate).

[0037] Step 1 involves the preparation of pre-deformed hot-rolled low-density steel substrate; Steel composition (mass fraction): C 0.82%, Mn 20.5%, Al 9.1%, balance Fe, S 0.015%, P 0.011%; smelting and casting into cylindrical ingots; homogenization annealing at 1200℃ to eliminate casting segregation, hot forging followed by air cooling; wire cutting to obtain initial thickness slabs; slabs subjected to through-heating at 1200℃ with differentiated heat treatment, hot rolling with a total reduction of 25%, uniformly rolled to the target thickness, final rolling temperature ≥900℃; rapid water cooling after rolling; low-temperature stress-relief annealing at 200~300℃; double-sided precision grinding to Ra≤1.6μm, ultrasonic cleaning and drying; Wire EDM machining of Φ8mm rotary bending fatigue specimens of the same specifications; TEM analysis of the microstructure in the hot-rolled state: dislocation density 1.3 × 10⁻⁶ 10 cm -2 The continuous and uniform deformation band runs through all grains. The average size of the κ carbide is 56 nm. The gradient distribution along the thickness direction is significant. The volume fraction of surface carbides is higher than that in the core. The plastic energy storage is moderate.

[0038] Step 2: Differentiated coupling matching laser shock process; The laser single pulse energy is 7J, the laser impact passes are 2, and the two scanning paths completely overlap. The peak pressure of the shock wave was 2.1 GPa. The absorption layer, constraint layer, light spot, overlap rate, pulse width, and laser wavelength are consistent with those in Example 1, all adopting a unified standard, and the energy and frequency dual parameters are synchronously controlled to balance the enhancement effect and tissue damage.

[0039] Step 3: Post-processing and performance testing; After impact, the aluminum foil was peeled off, ultrasonically cleaned with anhydrous ethanol for 5 minutes, and then dried with water. The following tests were conducted sequentially: residual stress gradient detection along thickness, TEM microstructure layering observation, and rotational bending fatigue life test at a stress amplitude of 450 MPa.

[0040] Detection results of Example 2: The maximum residual compressive stress on the surface of the steel sample is 442 MPa, the depth of the residual compressive stress layer is 106 μm, and the residual compressive stress at a depth of 80 μm is 275 MPa. The dislocation density on the surface of the steel sample increased to 8.6 × 10⁻⁶. 10 cm -2 The original hot-rolled continuous deformation zone and laser-induced dislocations interpenetrate to refine the subgrains; κ carbides maintain their complete nanoscale structure, and there are no cracks or pores at the interface between the carbides and the matrix. 10 7 The high-cycle fatigue life was improved by 178% compared to the unimpacted hot-rolled substrate. Comparison of two sets of traditional processes: Comparison 1 (traditional unified 3-pass 9J high energy): 1-5μm transgranular microcracks appeared on the surface, residual compressive stress relaxed and decayed, fatigue life was only improved by 82%, typical over-impact failure; Comparison 2 (traditional fixed 1-pass 5J low energy): insufficient plasticity modification depth, fatigue life increased by 114%; The evidence shows that the energy storage of the pre-deformed substrate is moderate. The medium-energy two-pass coupling scheme of this invention achieves performance balance. Adjusting only a single energy or pass will result in insufficient reinforcement or tissue damage.

[0041] Example 3 Laser shock strengthening and control of high hot-rolled pre-deformed Fe-Mn-Al-C low-density steel (total hot-rolling reduction of 68%, high pre-deformed substrate).

[0042] Step 1: Prepare a high-pre-deformation hot-rolled low-density steel substrate; Steel composition (mass fraction): C 0.94%, Mn 21.6%, Al 9.7%, balance Fe, S 0.011%, P 0.009%; smelting and casting into cylindrical ingots; homogenization annealing at 1200℃ to eliminate casting segregation, hot forging followed by air cooling; wire cutting to obtain initial thickness slabs; slabs subjected to through-heating at 1200℃ with differentiated heat treatment, hot rolling with a total reduction of 25%, uniformly rolled to the target thickness, final rolling temperature ≥900℃; rapid water cooling after rolling; low-temperature stress-relief annealing at 200~300℃; double-sided precision grinding to Ra≤1.6μm, ultrasonic cleaning and drying; Wire EDM machining of Φ8mm rotary bending fatigue specimens of the same specifications; TEM analysis of the microstructure in the hot-rolled state: dislocation density 2.7 × 10⁻⁶ 10 cm -2 The high-density interwoven deformation bands cover all grains, the average size of the ultrafine κ carbides is 32nm, the surface carbides are rich in a large amount, the hot-rolled pre-deformation has extremely high energy storage, and there are a large number of plastic deformation substructures inside the matrix.

[0043] Step 2: Differentiated coupling matching laser shock process; The laser single pulse energy is 5J, the laser impact channel is 1 channel, and only a single full-area scan is used for coverage. The peak pressure of the shock wave is 1.5 GPa; the absorption layer, the flowing water confinement layer, the spot diameter of 3 mm, the overlap rate of 50%, the pulse width of 15 ns, and the laser wavelength of 1064 nm all adopt the same standard, which greatly reduces the input energy and the number of impacts and avoids energy storage overload.

[0044] Step 3: Post-processing and performance testing; After laser shock, remove the aluminum foil, ultrasonically clean with anhydrous ethanol for 5 minutes, and then water-cool and dry. We conducted residual stress gradient detection along the thickness direction, transmission electron microscopy characterization of surface layer structure, and high-cycle fatigue test with 450 MPa stress amplitude rotational bending.

[0045] Example 3 Detection Results: The maximum residual compressive stress on the surface of the steel sample is 395 MPa, the depth of the residual compressive stress layer is 89 μm, and the compressive stress at a depth of 60 μm is stably maintained at 240 MPa. The dislocation density on the surface of the steel sample increased slightly to 5.3 × 10⁻⁶. 10 cm -2 Only a suitable amount of new dislocations are introduced on the basis of the original high-density deformation zone, without dislocation degree multiplication, without nano-κ carbide breakage and cracking, and without any microcracks or interlayer delamination defects in the surface and sub-surface layers. 10 7 The high-cycle fatigue life is 136% higher than that of non-impact hot-rolled base material, meeting the fatigue service index of lightweight aerospace structural components. Comparison of two sets of traditional unified parameters: Comparison 1 (traditional uniform 2 passes 7J energy): dense network microcracks are generated on the surface, the residual compressive stress is greatly reduced, the fatigue life is only increased by 41%, and severe over-impact failure occurs; Control 2 (traditional 3 passes 9J): The surface of the sample peeled off over a large area, completely losing its service performance; This invention demonstrates that the high-pre-deformation hot-rolled substrate itself possesses high-density dislocations and deformation energy storage. The low-energy single-pass mild strengthening scheme of this invention will inevitably cause irreversible structural damage in the existing fixed multi-pass high-energy process.

[0046] Example 4: Wide Component Range Adaptation Verification Example; Step 1: Substrate preparation; Steel composition (mass fraction): C 0.52%, Mn 15.8%, Al 7.7%, balance Fe, total trace impurities ≤0.03%; smelting and casting into cylindrical ingots; homogenization annealing at 1200℃ to eliminate casting segregation, hot forging followed by air cooling; wire cutting to obtain initial thickness slabs; slabs subjected to through-heating at 1200℃ with differentiated holding, hot rolling with a total reduction of 25%, uniformly rolled to the target thickness, final rolling temperature ≥900℃; rapid water cooling after rolling; low-temperature stress-relief annealing at 200~300℃; double-sided precision grinding to Ra≤1.6μm, ultrasonic cleaning and drying; machining of Φ8mm standard fatigue specimens; hot-rolled dislocation density 1.6×10⁻⁶. 10 cm -2 The average size of the κ carbide is 49 nm, and the deformation bands are uniformly and continuously distributed.

[0047] Step 2: Laser shock process matching; According to the pre-deformation grading matching criterion of the present invention, the single pulse energy is 7J, the number of impact passes is 2, and the other supporting conditions are completely the same as those in Example 1.

[0048] Step 3 Performance Test Results: The maximum residual compressive stress on the surface of the steel sample was 431 MPa, and the depth of the residual compressive stress layer was 102 μm; there were no surface microcracks or carbide interface debonding defects; 10 7 The cycle fatigue life is improved by 169% compared with the original hot-rolled base material; this proves that the graded coupling process of the present invention is applicable to all composition ranges of Fe-Mn-Al-C low-density steel, and is not affected by large fluctuations in C, Mn and Al content, and the process has strong universality and adaptability.

[0049] Comparative example: Traditional laser shock blasting process with uniform parameters and no differentiation; Three types of substrates were selected: low pre-deformation in Example 1, medium pre-deformation in Example 2, and high pre-deformation in Example 3. All of them adopted industry-standard fixed laser shock parameters: single pulse energy 7J, 2 shock passes; the absorption layer, constraint layer, spot size, and overlap rate remained unchanged, and the hot-rolled pre-deformation history was not distinguished.

[0050] Low pre-deformation substrate (raw material of Example 1) Traditional process: fatigue life is only improved by 105%, the residual compressive stress layer is shallow, and the strengthening is seriously insufficient; Pre-deformed substrate (raw material of Example 2) Traditional process: fatigue life is improved by 176%, but the microstructure of batches fluctuates greatly, carbides are locally broken, and product stability is poor; High pre-deformation substrate (raw material of Example 3) Traditional process: dense microcracks on the surface, fatigue life is only improved by 41%, and irreversible impact failure occurs; Comparison and summary: Existing laser shock peening relies solely on fixed parameters to treat all hot-rolled low-density steels, failing to recognize that the differences in initial microstructure and plastic energy storage gradient caused by hot-rolling pre-deformation will lead to polarized strengthening effects. There is no technology for controlling the process by classifying hot-rolling reduction amount and coupling laser energy and shock pass as dual variables.

[0051] This invention quantifies the microstructure characteristics of hot-rolled pre-deformed substrates and uses a three-level matching criterion to design laser input loads differently for different energy storage substrates. It simultaneously achieves: deep and sufficient strengthening of low-pre-deformed substrates, non-damaging modification of high-pre-deformed substrates, and balanced performance of medium-pre-deformed substrates. This solves the long-standing technical problem of being unable to balance "strengthening gain" and "surface structure integrity".

Claims

1. A method for controlling laser shock strengthening of low-density steel considering hot-rolled pre-deformation history, characterized in that, include: S1. Prepare Fe-Mn-Al-C low-density steel hot-rolled base material, wherein the chemical composition of the low-density steel, by mass fraction, is: C 0.5%~1.0%, Mn 15%~22%, Al 7.5%~10%, with the balance being Fe and trace impurities, and the total mass fraction of trace impurities S and P ≤0.03%; Based on the total hot-rolled reduction, the hot-rolled substrate is pre-deformed and classified into low-pre-deformed substrate, medium-pre-deformed substrate, and high-pre-deformed substrate. S2. Based on the microstructure and plastic energy storage characteristics of substrates with different pre-deformation grades, differentiated coupling and matching of dual process parameters: laser single pulse energy and laser shock pass. S3. Under the same laser shock conditions, laser shock strengthening with corresponding parameters is carried out on pre-deformed substrates of different grades. S4. After the impact, the sample is post-treated to obtain Fe-Mn-Al-C low-density steel components with no surface micro-damage, stable deep residual compressive stress, and high fatigue life.

2. The laser shock strengthening control method for low-density steel considering hot-rolled pre-deformation history according to claim 1, characterized in that: The pre-deformation grading standard mentioned in step S1 is: Low pre-deformation substrate: total hot rolling reduction ≤30%, matrix dislocation density <5×10 9 cm -2 The deformation bands are discontinuously and sparsely distributed, the size of the nano-κ carbides is 50-120 nm, the thickness gradient is weak, and the matrix has low plastic energy storage. Pre-deformed substrate: hot-rolled total reduction 30%–60%, matrix dislocation density 5×10⁻⁶ 9 ~2× 10 10 cm -2 The continuous and uniform deformation bands penetrate the grains, the size of the nano-κ carbides is 30-80 nm, the thickness gradient is significant, and the matrix has moderate plastic energy storage. High pre-deformation substrate: total hot rolling reduction > 60%, matrix dislocation density > 2 × 10⁻⁶ 10 cm -2 The high-density interwoven deformation bands are distributed throughout the grains, the nano-κ carbides are 20-50nm in size and highly enriched on the surface, and the matrix has high plasticity and energy storage.

3. The laser shock strengthening control method for low-density steel considering hot-rolled pre-deformation history according to claim 1, characterized in that: The criteria for matching differentiated processes in step S2 are as follows: Low pre-deformation substrate: matched with high single-pulse energy, 3-pass repetitive laser shock; Medium-deformation substrate: matched with medium single-pulse energy, 2-pass repetitive laser shock; High pre-deformation substrate: matched with low single-pulse energy, 1-pass single-shot laser shock.

4. The laser shock strengthening control method for low-density steel considering hot-rolled pre-deformation history according to claim 3, characterized in that: The single-pulse laser energy of the low pre-deformation substrate is 9J, and the peak pressure of the shock wave is 2.6GPa. The single-pulse laser energy of the pre-deformed substrate is 7J, and the peak pressure of the shock wave is 2.1GPa. The single-pulse laser energy of the high pre-deformation substrate is 5J, and the peak pressure of the shock wave is 1.5GPa.

5. The laser shock strengthening control method for low-density steel considering hot-rolled pre-deformation history according to claim 1, characterized in that: The unified laser shock conditions in step S3 include: An Nd:YAG pulsed laser with a wavelength of 1064 nm and a pulse width of 15 ns was used. A 150 μm high-purity aluminum foil was pasted on the sample surface as an absorption layer. A 1 mm thick continuously flowing deionized water layer was placed above the sample as a transparent constraint layer with a flow rate of 0.8 L / min. The laser spot diameter was 3 mm, and a square scanning path was used with an overlap rate of 50% between adjacent spots.

6. The laser shock strengthening control method for low-density steel considering hot-rolled pre-deformation history according to claim 1, characterized in that: The post-processing method described in step S4 is as follows: After laser shock, the aluminum foil was peeled off, and the sample was ultrasonically cleaned with anhydrous ethanol for 5 minutes, then water-cooled and dried for later use.

7. The laser shock strengthening control method for low-density steel considering hot-rolled pre-deformation history according to claim 1, characterized in that: The hot-rolling process for preparing low-density steel includes: The first step is alloy melting and casting; the alloy is prepared according to the target composition, melted in a vacuum induction melting furnace, and cast into cylindrical ingots. The second step is homogenization annealing and hot forging; the round ingot is homogenized at 1200℃ to eliminate casting segregation, and then multi-directional hot forging is performed to forge it into a shape with a uniform initial thickness H. 00 Square or rectangular billets are forged and then air-cooled to room temperature; The third step is to prepare slabs with different initial thicknesses by wire cutting. From the billet forged in the second step, several slabs with different initial thicknesses H0 are processed by wire cutting. This cutting method does not introduce any macroscopic plastic deformation, ensuring that all slabs perfectly inherit the consistent initial structure of the parent material. The fourth step is uniform firing and differentiated hot rolling; after all slabs are uniformly fired at 1200℃, different initial slab thicknesses are matched with different total hot rolling reduction rates, and all slabs are uniformly rolled to the same target plate thickness H. t Final rolling temperature ≥900℃; Method for determining the uniform temperature through-firing process: Place all slabs with different initial thicknesses H0 in the same heating furnace and heat them at the same target temperature of 1200℃. The holding time t of each slab is set according to the empirical formula t=k×H0, where k is the heating coefficient, with a value range of 1.0-2.0min / mm, and H0 is the initial thickness of the slab, in mm. When the target temperature T = 1150℃, and k = 1.5 min / mm is selected: For a slab with H0=12mm, the holding time is t=18min; For a slab with H0=20mm, the heat preservation time is t=30min; This formula ensures that the core of all slabs reaches the target temperature, so that all slabs obtain an initial microstructure with consistent proportions, uniform grain size, and uniform composition distribution, and completes austenite homogenization to obtain an initial microstructure with consistent grain size, while avoiding overheating of thin slabs or insufficient homogenization of thick slabs. The fifth step is to force rapid cooling to lock in the microstructure; after hot rolling, rapid water cooling to room temperature can suppress dislocation recovery, static recrystallization and large-scale precipitation of the second phase at high temperature, and stabilize the dislocation substructure and deformation energy storage generated by hot rolling plastic deformation. Step 6: Low-temperature stress relief; The cooled hot-rolled sheet is subjected to low-temperature recovery stress relief annealing to release only the macroscopic residual stress caused by hot rolling, while retaining the dislocation substructure, deformation energy storage and original phase distribution introduced by different hot rolling reduction amounts. Step 7, surface treatment; double-sided fine grinding, controlling the roughness Ra≤1.6μm, the surface presents a uniform and delicate matte surface, ultrasonic cleaning with anhydrous ethanol for 15min to remove oil and grinding debris, and drying; Step 8: Differentiated laser shock.